Effect of ileal bile acid transporter inhibitor GSK2330672 on pruritus in primary biliary cholangitis: a double-blind, randomised, placebo-controlled, crossover, phase 2a study. Issue 10074 (18th March 2017) - Hegade, Vinod S; Kendrick, Stuart F W; Dobbins, Robert L; Miller, Sam R; Thompson, Douglas; Richards, Duncan; Storey, James; Dukes, George E; Corrigan, Margaret; Oude Elferink, Ronald P J; Beuers, Ulrich; Hirschfield, Gideon M; et al.
Summary: Background: Up to 70% of patients with primary biliary cholangitis develop pruritus (itch) during the course of their disease. Treatment of pruritus in primary biliary cholangitis is challenging and novel therapies are needed. Ursodeoxycholic acid, the standard first-line treatment for primary biliary cholangitis, is largely ineffective for pruritus. We investigated the efficacy and safety of GSK2330672, a selective inhibitor of human ileal bile acid transporter (IBAT), in patients with primary biliary cholangitis with pruritus. Methods: We conducted this phase 2a, double-blind, randomised, placebo-controlled, crossover trial in two UK medical centres. Following 2 weeks of open placebo run-in, patients were randomly assigned in a 1:1 ratio with a block size of 4 to receive GSK2330672 or placebo twice daily during two consecutive 14-day treatment periods in a crossover sequence. The treatment periods were followed by a 14-day single-blinded placebo follow-up period. The primary endpoints were safety of GSK2330672, assessed using clinical and laboratory parameters, and tolerability as rated by the Gastrointestinal Symptom Rating Scale. The secondary endpoints were changes in pruritus scores measured using the 0 to 10 numerical rating scale (NRS), primary biliary cholangitis-40 (PBC-40) itch domain score and 5-D itch scale, changes in serum total bile acids and 7 alpha hydroxy-4-cholesten-3-one (C4), and changes in the pharmacokinetic parameters of ursodeoxycholic acid and its conjugates. The trial was registered withClinicalTrials.gov, numberNCT01899703 . Findings: Between March 10, 2014, and Oct 7, 2015, we enrolled 22 patients. 11 patients were assigned to receive intervention followed by placebo (sequence 1), and 11 patients were assigned to receive placebo followed by intervention (sequence 2). One patient assigned to sequence 2 withdrew consent prior to receiving randomised therapy. One patient did not attend the placebo follow-up period, but was included in the final analysis. GSK2330672 treatment for 14 days was safe with no serious adverse events reported. Diarrhoea was the most frequent adverse event during treatment with GSK2330672 (seven with GSK2330672 vs one with placebo) and headache was the most frequent adverse event during treatment with placebo (seven with placebo vs six with GSK2330672). After GSK2330672 treatment, the percentage changes from baseline itch scores were −57% (95% CI −73 to −42, p<0·0001) in the NRS, −31% (−42 to −20, p<0·0001) in the PBC-40 itch domain and −35% (−45 to −25, p<0·0001) in the 5-D itch scale. GSK2330672 produced significantly greater reduction from baseline than the double-blind placebo in the NRS (−23%, 95% CI −45 to −1; p=0·037), PBC-40 itch domain, (−14%, −26 to −1; p=0·034), and 5-D itch scale (−20%, −34 to −7; p=0·0045). After GSK2330672 treatment, serum total bile acid concentrations declined by 50% (95% CI −37 to −61, p<0·0001) from 30 to 15 μM, with a significant 3·1-times increase (95% CI 2·4 to 4·0, p<0·0001) in serum C4 concentrations from 7·9 to 24·7ng/mL. Interpretation: In patients with primary biliary cholangitis with pruritus, 14 days of ileal bile acid transporter inhibition by GSK2330672 was generally well tolerated without serious adverse events, and demonstrated efficacy in reducing pruritus severity. GSK2330672 has the potential to be a significant and novel advance for the treatment of pruritus in primary biliary cholangitis. Diarrhoea, the most common adverse event associated with GSK2330672 treatment, might limit the long-term use of this drug. Funding: GlaxoSmithKline and National Institute for Health Research.